The Role Of Zakat In Reducing Poverty And Income Inequality Among New Convert (Muallaf) In Selangor, Malaysia - Fuadah Johari; Muhammad Ridhwan Ab. Aziz; Ahmad Fahme Mohd Ali (Akademi Pengajian Islam, Universiti Malaya, 2024)
Online Journal of Research in Islamic Studies 1(3) (2014): 43-56